Pengaruh Kualitas Laba, Kebijakan Dividen, dan Cash Holdings Terhadap Kinerja Keuangan Pada Sektor Energi Yang Terdaftar di Bei Tahun 2020-2024 - Diana Safira; Asnahwati (ProBisnis : Jurnal Manajemen, 2025)
This study analyzes the influence of Profit Quality, Dividend Policy, and Cash Holdings on Financial Performance of energy sector companies. Using a quantitative approach with regression analysis, this research aims to test for partial and simultaneous relationships. The results of the partial tests show significant findings. Profit Quality has a negative and significant effect on Financial Performance (t-statistic = -93.373; sig = 0.000), indicating that lower profit quality can harm performance. Similarly, Dividend Policy has a negative and significant effect (t-statistic = -43.320; sig = 0.000), implying that higher dividend payouts can reduce funds for investment and negatively impact performance. In contrast, Cash Holdings have a positive and significant effect (t-statistic = 94.891; sig = 0.000), demonstrating that higher cash reserves can improve financial performance. Simultaneously, the three variables combined have a significant influence on Financial Performance (sig = 0.000). The research model is considered a good fit, with very high predictive power. This conclusion affirms that Profit Quality, Dividend Policy, and Cash Holdings are crucial factors that collectively influence financial performance in the energy sector.